2018
DOI: 10.1042/bcj20170649
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of LIMD1–VHL–HIF-1α–VEGF pathway is associated with different stages of cervical cancer

Abstract: To understand the mechanism of cellular stress in basal-parabasal layers of normal cervical epithelium and during different stages of cervical carcinoma, we analyzed the alterations (expression/methylation/copy number variation/mutation) of HIF-1α and its associated genes LIMD1, VHL and VEGF in disease-free normal cervix ( = 9), adjacent normal cervix of tumors ( = 70), cervical intraepithelial neoplasia (CIN; = 32), cancer of uterine cervix (CACX; = 174) samples and two CACX cell lines. In basal-parabasal lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Previous studies have suggested that LIMD1 participates in tumor progression of diverse cancers by serving as a tumor‐suppressor, such as in gastric cancer and cervical cancer . Also, LIMD1 is revealed by former studies to present low expression and hinder tumor growth In NSCLC .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have suggested that LIMD1 participates in tumor progression of diverse cancers by serving as a tumor‐suppressor, such as in gastric cancer and cervical cancer . Also, LIMD1 is revealed by former studies to present low expression and hinder tumor growth In NSCLC .…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies reveal that deletion of LIMD1 results in aberrant cellular behaviors, such as cell cycle perturbation and hyperproliferation of cells . The tumor‐suppressive impact of LIMD1 is supported by studies in multiple cancers, such as gastric cancer and cervical cancer . In NSCLC, evidence proves that LIMD1 is downregulated and results in the misregulation of retinoblastoma protein (pRB) and cell cycle .…”
Section: Introductionmentioning
confidence: 99%
“…HIFs mainly increase the angiogenesis, and cause the progression of the tumor in an aggressive course (46,48). The literature has revealed a signifi cant association between low surveillance and high HIF1α levels in patients with bladder, breast, endometrial, cervical, oropharyngeal and esophageal carcinomas (45,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). In addition, HIF1α has been reported to be associated with poor prognosis in pancreatic tumors (62).…”
Section: Discussionmentioning
confidence: 99%
“…LIMD1 is a member of the Zyxin proteins, encoded at chromosome 3p21.3 and widely expressed in human tissues (22,23). A large number of previous studies have suggested that LIMD1 functions as a tumor suppressor (24)(25)(26)(27). In terms of molecular mechanism, LIMD1 could participate in cellular processes and pathways through its scaffold function, meaning that the tumorsuppressive function of LIMD1 is likely to be regulated by different signal cascades (28).…”
Section: Discussionmentioning
confidence: 99%